The effect of the Messinian salinity crisis on the early diversification of the Tettigettalna cicadas. (8th October 2022) - Costa, Gonçalo J.; Nunes, Vera L.; Marabuto, Eduardo; Mendes, Raquel; Silva, Diogo N.; Pons, Pere; Bas, Josep M.; Hertach, Thomas; Paulo, Octávio S.; Simões, Paula C.
Abstract: The current distribution patterns of many Mediterranean species are often a consequence of large and impactful past geoclimatic events, such as the Messinian Salinity Crisis (MSC) and the Quaternary glacial cycles. Cicadas are flying insects with poor dispersal ability, which have experienced intense local differentiation in the Mediterranean, where the genus Tettigettalna has surfaced as a biogeographic model. The genus includes 10 species with species‐specific calling songs but identical morphology. All Tettigettalna species are restricted to Southern Iberia, with the exception of T. estrellae (northwest Iberia), the widespread T. argentata (mainly Iberia, France and Italy), and T. afroamissa (Morocco). With an expanded genetic dataset involving nuclear ( EF1α ) and mitochondrial (5′ and 3′ COI and ATP ) loci, we reconstructed the phylogeny of the genus and estimated divergence dates for Tettigettalna species under a Bayesian framework. Phylogeny with the new mitochondrial dataset was in agreement with previous studies, whereas the nuclear EF1α supported T. josei and T. afroamissa as monophyletic clades but lacked resolution to resolve the remaining taxa. Some sister taxa share mitochondrial haplotypes, hinting for incomplete lineage sorting. Estimates of divergence time settled T. josei as the earliest diverging lineage, likely as a pre‐ or early‐MSC event. As for the origin of T. afroamissa in Morocco, though time estimates could not entirely rule out post‐MSC dispersal, the most likely scenario points to isolation of African Tettigettalna after the reopening of the strait of Gibraltar. The Pleistocene glaciations that followed likely impacted on the diversification of the remaining species of the genus in southern Iberia refugia.